2022
DOI: 10.3389/fpsyg.2022.901085
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership and Employee Resilience: A Moderated Mediation Analysis

Abstract: Authentic leadership is essential for predicting employee resilience. However, despite fruitful findings, more adapted models of authentic leadership – employee resilience based on empirical findings can serve as a guide to understand the complex mediators and moderators in different industries such as in construction engineering project organizations during the turbulent pandemic. This study, therefore, based on the organizational identification theory and flow theory through the lens of positive organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 93 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…However, certain variables can impact the negative relationship between PSS and turnover intention. Although some scholars suggested organizational identification as an intervening variable of the relationship between authentic leadership and outcomes ( Mao et al, 2022 ), we propose that organizational identification plays an important moderating role in the effect of authentic leadership on turnover intention. Social identity theory suggests that organizational identification can contribute to employees’ attitudes and behaviors such as OCB, job satisfaction, commitment, and turnover intention.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 73%
See 1 more Smart Citation
“…However, certain variables can impact the negative relationship between PSS and turnover intention. Although some scholars suggested organizational identification as an intervening variable of the relationship between authentic leadership and outcomes ( Mao et al, 2022 ), we propose that organizational identification plays an important moderating role in the effect of authentic leadership on turnover intention. Social identity theory suggests that organizational identification can contribute to employees’ attitudes and behaviors such as OCB, job satisfaction, commitment, and turnover intention.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 73%
“…For example, scholars found that authentic leadership is positively associated with organizational level constructs such as employees’ affective attachment to and organizational identification ( Leroy et al, 2012 ). Most importantly, studies revealed that organizational identification mediates the relationship between authentic leadership and employee resilience using a theoretical framework that organizational identification can be influenced by their leaders (e.g., Mao et al, 2022 ). In this study, we aim to gain a better understanding of how authentic leaders reduce employee turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological resilience can be developed in the presence of proper leadership and help employees recover from adversity (Franken et al, 2020). In line with the principle of reciprocity and social exchange theory, Mao et al (2022) discovered that authentic leadership was significantly related to employee psychological resilience. Eliot (2020) explored that servant leaders focus their efforts on meeting their followers' psychological needs and are thus well positioned to positively impact subordinate psychological resilience (Eliot, 2020).…”
Section: Inclusive Leadership and Employee Psychological Resiliencementioning
confidence: 90%
“…Leadership style is the situational factor that has the greatest impact on the behavior of subordinates ( Owens and Hekman, 2016 ). Leadership style can effectively guide the behavior of employees and is seen as an essential trigger factor for psychological resilience ( Zhu et al, 2019 ; Franken et al, 2020 ; Mao et al, 2022 ). When a leader has the right leadership style, people can develop psychological resilience, which can help them recover from stressful situations ( Franken et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It corresponded to the dimensions of flow as described by Csikszentmihalyi (1975) and was designed to assess the frequency of participants' flow experience for each of the three distinct contexts (i.e., work, maintenance and leisure). The SFPQ has demonstrated robust reliability and validity across different cultural contexts and diverse populations, including university students (Mao et al., 2022; Wu et al., 2021). The sample items in this study include: ‘When you engage in study activities, how often do you experience a sense of complete control?’ and ‘When you engage in study activities, how often do you find yourself completely focused?’ According to recommendations, all factor loadings based on the confirmatory factor analysis (CFA) should ideally be .5 or above (Hair et al., 2006).…”
Section: Methodsmentioning
confidence: 99%